Therapeutic Effects of Biobran, Modified Arabinoxylan Rice Bran, in Improving Symptoms of Diarrhea Predominant or Mixed Type Irritable Bowel Syndrome: A Pilot, Randomized Controlled Study - Kamiya, Takeshi (Hindawi Publishing Corporation, 2014)
Background. Recently, it was revealed that low grade mucosal inflammation and/or immune imbalance of the lower digestive tract is one of the mechanisms involved in symptom generation in patients with irritable bowel syndrome (IBS). Biobran, arabinoxylan compound derived from rice bran, has been reported to have several biological actions such as anti-inflammatory and immune modulatory effects. So we investigated the therapeutic effects of Biobran in patients with IBS. Method. Forty patients with diarrhea predominant or mixed type IBS were randomly assigned to either a Biobran group for treatment with Biobran or a placebo group. Therapeutic efficacy and IBS symptoms were assessed subjectively by the patients after 4 weeks of administration. Results. The global assessment was effective in 63.2% of the Biobran group and in 30% of the placebo group (P < 0.05, Biobran group versus placebo group). Biobran group showed a significant decrease in the score of diarrhea and constipation and in CRP value. However, no significant changes were observed in the placebo group. Conclusion. The administration of Biobran improved IBS symptoms. It is likely that anti-inflammatory and/or immune modulatory effects of Biobran might be useful in IBS patients.